DESIGN ANALYSIS OF AN AUTOMATIC PHASE SELECTOR - ADEDOTUN O. OWOJORI; ABIODUN M. AKINBOLADE; KAYODE F. AKINGBADE (Journal of Engineering Studies and Research)
Power instability in Nigeria caused by overbearing demand of power by consumers and lack of proper maintenance of the power system devices among others has brought about the need for alternative power sources such as generators, solar, typical inverters and other alternative supplies which requires one form of switching or the other to achieve phase selection during power failure. This paper gives a design analysis of an automatic phase selector linking available power supplies, that is; switching between a three-phase public utility supply, as a result of total power outage in the public supply to an alternative secondary supply (in this case a Generator and an Inverter system) and back when power is restored. The design adopts the use of a microcontroller-based system interconnected with other hardware components for proper isolation, switching and visualization of switching conditions. The system design is divided into two major part: the hardware which consists of the power supply, sensing circuit, controller or control logic circuit, display and the power electronics switching unit and the software instruction code on the microcontroller unit. The design analysis was first carried out accompanied with computer simulation on a software tool (Proteus 8 Professional, version 8.4) to carry out performance evaluation of the sub-circuits, thereafter, a practical implementation of the design was carried out and tested with the utility power supply using five (5) switches, three of which represents the three-phase primary supply and the other two represents the secondary supply.